The Great Divergence: A Network Approach - Ines Lindner; Holger Strulik (Center for Economic Studies and ifo Institute (CESifo), 2015)
We present a multi-country theory of economic growth in which countries are connected by a network of mutual knowledge exchange. Knowledge in any country depends on the human capital of the countries it exchanges knowledge with. The diffusion of knowledge throughout the world explains a period of increasing world inequality after the take-off of the forerunners of the industrial revolution, followed by decreasing relative inequality. Knowledge diffusion through a Small World network explains the `New Kaldor facts' and produces an extraordinary diversity of country growth performances, including the overtaking of individual countries in the course of world development.
Keywords: O10; O40; D62; D85; F41; 330; networks; knowledge diffusion; economic growth; world income distribution